2011
DOI: 10.1007/s11135-010-9424-7
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the application of 6-Sigma on the enhancement of service quality of fitness club

Abstract: The service industry plays an essential role in economic globalization and a determining factor in strengthening industry's competitiveness. Targeting fitness industry, this study intends to explore ways to minimize customer complaints, understand customer expectation, and enhance service quality by applying the five steps of 6-Sigma: (1) Definition; (2) Measurement; (3) Analysis; (4) Improvement; and (5) Control, to effectively solve the root causes of customer complaints, raise customer satisfaction and mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…An initial desk research reviewing cross-sectorial literature on scientific fields such as service quality models (Parasuraman et al, 1985;Cheng et al, 2012); customer satisfaction in health and fitness centers (MacIntosh and Doherty, 2007;Barros and Gonçalves, 2009;Fernández et al, 2014) and perceptual phenomenology (Nanay, 2012), revealed the need to expand the construct. The 7P model became the 8P model with the integration of a new elementperception.…”
Section: Methodsmentioning
confidence: 99%
“…An initial desk research reviewing cross-sectorial literature on scientific fields such as service quality models (Parasuraman et al, 1985;Cheng et al, 2012); customer satisfaction in health and fitness centers (MacIntosh and Doherty, 2007;Barros and Gonçalves, 2009;Fernández et al, 2014) and perceptual phenomenology (Nanay, 2012), revealed the need to expand the construct. The 7P model became the 8P model with the integration of a new elementperception.…”
Section: Methodsmentioning
confidence: 99%
“…(Surange, 2015). Otros investigadores han utilizado la métrica sigma para analizar el desempeño de servicios en una institución de educación en Ecuador (Reyes, Fernández, Pérez y Urrutia, 2018) Los investigadores (Cheng, Hsu y Huang, 2012) desarrollaron un método con el fin de reducir las quejas de los clientes, comprendiendo las expectativas de los clientes y mejorando la calidad del servicio por medio de los conceptos de Seis Sigma. Los investigadores (Klefsjö, Wiklund y Edgeman, 2001) cuando aplicaron Seis Sigma y el uso intensivo de las métricas estadísticas, con un enfoque de innovación tuvieron resultados significativos en términos de gerencia y mejoras organizacionales.…”
Section: Seis Sigma En El Serviciounclassified
“…Corporate values focused on sales tend to affect staff turnover, increasing staff intention to leave (MacIntosh, Doherty, & Walker, 2010). In order to maintain customer satisfaction continued participation in fitness clubs, Chen, Hsu, and Huang (2012) demonstrate how to the apply 6-Sigma to enhance the service quality of fitness clubs, while Wilson (2009) provides guidelines for effective fitness center websites.…”
Section: Marketing Of Fitness Centersmentioning
confidence: 99%